Fire regimes and pollinator behavior explain the genetic structure of Puya hamata (Bromeliaceae) rosette plants - Montúfar, Rommel (Dryad, 2019)
The demography of the Andean Puya hamata has been linked to fire regimes
and hummingbird behaviour, which might modify the plant’s population
genetic diversity. Naturally poor dispersal results in patches of
genetically related plants, a pattern intensified further by burning which
promotes seedling germination around parent plants. Later, when these
plants flower, large patches are attractive to territorial hummingbirds
which prevent visits by traplining hummingbird species, carrying pollen
from likely unrelated plants. To explore this hypothesis, a genetic study
of P. hamata using microsatellite markers was conducted with (i) isolated
and grouped adults in two size categories of patches, and (ii) seeds
collected from the same patches and isolated individuals. Isolated
individual plants were most genetically diverse with close to zero
endogamy. Adult plants from large patches showed, lower diversity and
higher endogamy than plants from other spatial contexts. Seed genetic
structure displayed a gradient of diversity: lower at patch centres but
higher at patch edges, in small patches and for isolated infructescences.
The spatial context of these plants, especially the contrast between large
patch centres and other situations, determines the genetic diversity of
their seeds via hummingbird foraging behaviour. Territorial hummingbirds
restrict gene flow in and out of large patches, but traplining
hummingbirds maintain genetic diversity among isolated plants, small
patches and plants at the edges of large patches. Our study illustrates
the need to consider interactions between land use, plants and their
pollinators when considering genetic diversity at the landscape scale.
Keywords: pollinators; fire regimes; Puya hamata